Ultrasonic Fabrication of Polymer Plate Reactors with a Surface Coating. Issue 5 (7th February 2019) - Hoehr, Lukas; Reichmann, Felix; Berndt, Marius; Sackmann, Johannes; Kockmann, Norbert; Schomburg, Werner Karl
Abstract: Microreactors offer several advantages compared to the industrial scale when developing new chemical processes. Especially the production and investment costs are low if polymer microreactors are generated by ultrasonic processes. In order to observe the chemical reaction and the flow configuration, these microreactors need to be optically transparent, mechanically stable, and chemically inert to several reagents. The manufacturing process of a transparent polymer plate reactor with a chemically inert surface coating by ultrasonic fabrication is described. Experimental characterization of the microreactors showed that they are leak tight up to a pressure difference of at least 300 kPa and the mixing times are in the range of milliseconds. Abstract : A polymer plate reactor was generated from two different polymers. By ultrasonic fabrication, a transparent polymer plate was welded with a chemically inert polymer layer. The leak‐tight reactor system can withstand all tested flow rates and resulting pressures, with rapid and efficient mixing in the range of milliseconds.